Geomorfologi Sungai Klawing Daerah Bobotsari, Kabupaten Purbalinggga, Jawa Tengah - Asmoro Widagdo (Dinamika Rekayasa, 2012)
Klawing watershed is in Banyumas basin area, Purbalingga, Central Java. The river's flow is cut Tertiary rocks in the mountains of North Serayu, which includes Halang Formation, Kumbang, and Tapak and also Quaternary volcanic rocks of Slamet Volcano. The morphology of the surrounding area of the river is a volcanic mountains of Slamet Volcano in the western, homocline mountainous in the north and the hills / plains in the east and south. Geomorphological processes of Klawing River has formed alluvial deposition and the plain around the river. Alluvial deposits form the terrace around the Klawing River. At least three terrace rivers developed around the study area. The three terrace rivers are each up to elevations of 2.9 m, 22.9 m and 34.9 m from the surface of the Recent river.